2021
DOI: 10.1108/hff-11-2020-0745
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility analysis of the couple stress hybrid nanofluid flow under the effect of electromagnetic field

Abstract: Purpose This paper aims to consider the heat transportation together with irreversibility analysis for the flow of couple stress hybrid nanofluid past over a stretching surface. The innovative characteristics of this paper include electro-magnetohydrodynamic (EMHD) term, viscous dissipation, Joule heating and heat absorption\omission. The hybrid nanofluid is prepared due to the suspension of the solid nanoparticles of the single wall and multi-wall carbon nanotubes (SWCNTs and MWCNTs) in the blood for the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…The technique of finite-difference is utilized to resolve it numerically. Newly, the employability of maximized energy loss and other physical phenomena is located in the works of Khan et al 26 , Sheikholeslami et al 27 , Zeeshan et al 28 , Ahmad et al 29 , Moghadasi et al 30 , Shorbagy et al 31 , Ibrahim et al 32 – 35 , Majid et al 36 , Gul et al 37 , 38 , Wajdi et al 39 , Arshad Khan et al 40 , Jawad et al 41 and Saeed et al 42 .…”
Section: Introductionmentioning
confidence: 99%
“…The technique of finite-difference is utilized to resolve it numerically. Newly, the employability of maximized energy loss and other physical phenomena is located in the works of Khan et al 26 , Sheikholeslami et al 27 , Zeeshan et al 28 , Ahmad et al 29 , Moghadasi et al 30 , Shorbagy et al 31 , Ibrahim et al 32 – 35 , Majid et al 36 , Gul et al 37 , 38 , Wajdi et al 39 , Arshad Khan et al 40 , Jawad et al 41 and Saeed et al 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Entropy is an essential idea in engineering, mathematical models, and physics. It plays a vital role in continuum physics, thermodynamics, biology, and economics. − Entropy is actually a phenomenon dependent on the second law of thermodynamics, which states that entropy increases in an isolated system through any activity. While this idea is further extended in quantum mechanics with the inclusion of a density matrix.…”
Section: Formationmentioning
confidence: 99%
“…Chahregh et al 18 examined how a biological composite hybrid nano liquid made up of pure blood as the base fluid and TiO 2 and Ag nanomaterials could be transported via an artery. The blood flow rather than closed channels are studied by the researchers in [19][20][21] for testing purposes in medical laboratories. Liu et al 22 suggested a Pt/TiO 2 nano-size particles for cancer cell therapy because noble metal particles are thought to improve TiO 2 nanoparticles' photocatalytic operation.…”
Section: List Of Symbols U Vmentioning
confidence: 99%